2017
DOI: 10.1002/bmc.4135
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and measurement of serotonin

Abstract: Serotonin, also known as 5-hydroxytryptamine, is an important signaling molecule in the central and peripheral nervous systems of humans. Acting through several receptor types, it helps regulate the normal functioning of the gastrointestinal tract, cardiovascular system and brain. Serotonin signaling has also been implicated in the etiology of several diseases, including depression, anxiety disorders, hypertension and irritable bowel syndrome. The present review focuses on the chemical analysis of serotonin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 143 publications
0
22
0
1
Order By: Relevance
“…Clinical translation of these in vitro results to in vivo studies is not straightforward due to the low concentration of in vivo serotonin. Serotonin concentrations in human biological fluids have been measured as high as 283 ng/mL in whole blood 46 and in rat brain tissue as high as 29.5 ng/mg in the dorsal raphe nucleus, 47 which is approximately equivalent to 1.6 µM and 0.17 mM, respectively. However, the techniques used to measure serotonin concentration are uncertain, because they rely on extensive ex vivo tissue preparations that may significantly alter biochemical composition and do not accurately represent in vivo concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical translation of these in vitro results to in vivo studies is not straightforward due to the low concentration of in vivo serotonin. Serotonin concentrations in human biological fluids have been measured as high as 283 ng/mL in whole blood 46 and in rat brain tissue as high as 29.5 ng/mg in the dorsal raphe nucleus, 47 which is approximately equivalent to 1.6 µM and 0.17 mM, respectively. However, the techniques used to measure serotonin concentration are uncertain, because they rely on extensive ex vivo tissue preparations that may significantly alter biochemical composition and do not accurately represent in vivo concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that 5-HT plays a significant role in determining the characteristics of CSC. For example, reduced 5-HT concentrations have been observed in patients with depression and panic attacks [26]. With respect to CSC, Sakai et al reported a mean blood 5-HT concentration of 98.2 ± 27.5 ng/mL in 34 patients with chronic CSC, which was significantly lower than those in 31 normal controls (128.5 ± 35.8 ng/mL) and 15 patients with acute CSC (122.5 ± 23.9 ng/mL) [19].…”
Section: Discussionmentioning
confidence: 99%
“…The open field test showed discrete differences between motor locomotion and social behavior expressed through anxiety/fear when comparing male and female control groups and groups treated with diacetyl. Females are less vulnerable to stress than males [ 55 ], but they are more affected by repeated stress than males [ 56 ]. Such behavioral changes may be related to changes in metabolic profile.…”
Section: Discussionmentioning
confidence: 99%